2005
DOI: 10.1017/s0001924000000725
|View full text |Cite
|
Sign up to set email alerts
|

Kite performance testing by flying in a circle

Abstract: With the advent of recreational sports like kite surfing and buggying, the performance of kites has become a market driven item. Producers increasingly require methods to measure and improve the performance of the kites they manufacture. The Mechanical Engineering Department at the University of Canterbury has been working with a local kite producer to develop testing procedures suitable for kite manufacturers. The primary performance measurement is the lift to drag ratio. An early test rig was mounted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…3. Therefore, the rotating period of a rope kite can be controlled by the length of the tail pendant and towing line, as well as the lifting force by the cord of the rope kite in relation to the angle of attack (Stevenson et al, 2005;Houska and Diehl, 2006;Sánchez, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Therefore, the rotating period of a rope kite can be controlled by the length of the tail pendant and towing line, as well as the lifting force by the cord of the rope kite in relation to the angle of attack (Stevenson et al, 2005;Houska and Diehl, 2006;Sánchez, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The 20 cm cord length was determined based on the stiffness of the rope. This underwater rope kite has a lifting force with an adjustable angle of attack using the two bridle lengths; it can also rotate counterclockwise in response to the imbalance between the lifting force and the weight of the tail pendant, similar to the lateral circling motion of a kite in the air (Stevenson et al, 2005;Houska and Diehl, 2006;Sánchez, 2006). This imbalance, which works as a lifting force, results in differences between the leading edge and trailing edge of the rope kite and consequently in shearing force as the rope kite rotates (Diehl et al, 2004;Canale et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Fundamentals of kite performances and dynamics, i.e. the major forces which act on the flying kite, are described by [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Previous papers by the authors (1,2) have presented the fundamentals of measuring kite performance using circular flight tests. These have demonstrated that the method can provide more accurate results than traditional testing methods, such as stationary flight in natural wind or car-based tests in still air (3) .…”
Section: Introductionmentioning
confidence: 99%